2020
DOI: 10.21203/rs.3.rs-63386/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic value of plasma neurofilament light: A multicentre validation study

Abstract: Increased cerebrospinal fluid neurofilament light (NfL) is a recognized biomarker for neurodegeneration that can also be assessed in blood. Here, we investigate plasma NfL as a marker of neurodegeneration in fifteen neurodegenerative diseases from two multicenter cohorts: King’s College London (n = 847) and the Swedish BioFINDER study (n = 1464). Plasma NfL was significantly increased in all cortical neurodegenerative disorders, amyotrophic lateral sclerosis and atypical parkinsonian disorders. We further demo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…The study included consecutive patients with a clinical diagnosis of probable DLB and a subset of prodromal cases who underwent an extensive motor, cognitive and behavioral assessment. We demonstrated that clinical DLB cases exhibited increased plasma NfL levels compared with controls, in line with several cross-sectional studies focused on neurodegenerative disorders [7,19]. Furthermore, the findings showed that cases who retrospectively fulfilled the newly proposed prodromal DLB criteria [3] exhibited already increased plasma NfL levels compared with controls.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The study included consecutive patients with a clinical diagnosis of probable DLB and a subset of prodromal cases who underwent an extensive motor, cognitive and behavioral assessment. We demonstrated that clinical DLB cases exhibited increased plasma NfL levels compared with controls, in line with several cross-sectional studies focused on neurodegenerative disorders [7,19]. Furthermore, the findings showed that cases who retrospectively fulfilled the newly proposed prodromal DLB criteria [3] exhibited already increased plasma NfL levels compared with controls.…”
Section: Discussionsupporting
confidence: 87%
“…Neurofilament light chain (NfL), a highly expressed protein in large caliber myelinated axons, has been recently proposed as general marker of neuronal degeneration and damage in different neurological disorders [7,8]. In fact, CSF and plasma NfL levels are significantly altered in Alzheimer’s disease (AD), prion diseases, amyotrophic lateral sclerosis, frontotemporal dementia, whereas findings in Parkinson’s disease (PD) and early DLB were contradictory [9].…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques, however, have greatly guided the rapid discovery and validation of blood biomarkers for AD pathology, measured by ultra‐sensitive immunoassays or mass spectrometry methods. Recent studies have shown plasma measures to relate to Aβ deposition, 6–8 astrogliosis 9 and neurodegeneration 10–13 . Tau phosphorylated at threonine181 (P‐tau181) may be the most clinically meaningful plasma biomarker in AD to date, and multiple studies performed in independent cohorts demonstrate its high specificity for AD, strong associations with Aβ and tau PET, and high accuracy for predicting progression from mild cognitive impairment (MCI) to AD dementia 14–19 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated NfL in CSF to identify and monitor neuronal damage and have shown that NfL levels increase in response to neuronal damage, making it a promising biomarker for differentiating neurodegeneration from healthy aging ( Zetterberg et al, 2016 ; Fortea et al, 2018 ; Rojas et al, 2018 ; Bridel et al, 2019 ). Blood NfL is robustly increased in AD ( Mattsson et al, 2017 ; Lin et al, 2018 ; Ashton et al, 2019b ; Preische et al, 2019 ) but is also increased in many other neurodegenerative disorders and acute neurological disorders ( Hansson et al, 2017 ; Ehler et al, 2019 ; Hendricks et al, 2019 ; Mattsson et al, 2019 ; Ashton et al, 2020 ; Kapoor et al, 2020 ; Wihersaari et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%